TINGKAT PENGETAHUAN FINANSIAL TEKNOLOGI PADA PELAKU UMKM DI RUMAH MAKAN BINTANG KEJORA JAYA - Fauzia, Amanda Rizki; Andrian Noviardy (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study aims to explore the level of financial technology knowledge among MSMEs at the Bintang Kejora Jaya Restaurant through in-depth interviews. Data were collected from two informants, the restaurant manager and the cashier, regarding their experiences, understanding, and practices in using financial technology in managing their businesses. The results indicate that MSMEs understand the use of digital wallets and digital transaction recording, but are still limited in their understanding of capital management, investment, and financial risk. These findings emphasize the need for technology-based financial literacy mentoring and training for MSMEs.